Green accounting and firm value: The moderating role of external assurance in Indonesia - Wiguna, Nandina Putri; Sriwidharmanely, Sriwidharmanely; Usman, Berto (Jurnal Akuntansi dan Auditing Indonesia, 2026)
This study examines the effect of green accounting on firm value and the moderating role of external assurance in energy sector firms listed on the Indonesia Stock Exchange during 2017–2023. Using a quantitative approach, panel data regression with a Random Effect Model and robust standard errors is applied to 82 firm-year observations after outlier treatment using the Z-score method. Green accounting is measured using GRI-based environmental disclosure, while firm value is proxied by Tobin’s Q. The results show that green accounting has a marginally significant negative effect on firm value. However, external assurance significantly strengthens and reverses this relationship, indicating the importance of credibility in sustainability reporting. The findings extend signaling theory by demonstrating that environmental disclosure enhances firm value only when supported by independent verification. This study highlights the contingent role of assurance in shaping market interpretation of sustainability information in emerging markets. The analysis is limited to the energy sector, suggesting avenues for broader future research.